PENGARUH PEMBIASAAN SALAT DUHA TERHADAP KEDISIPLINAN SISWA AGAMA KELAS XI MAN 2 LANGKAT - Khairun Nida; Nurmisda Ramayani; Muhizar Muchtar (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
This research is motivated by the negative behavior of students which in general has been very disturbing lately and in the internal environment of the madrasah, violations of madrasah rules and regulations are still often found, such as: not wearing a complete school uniform, fighting, bullying, cheating and various other deviant behavior. Many madrasah schools have implemented the habit of duha prayer in their madrasahs, one of which is Man 2 Langkat. The purpose of this research is to find out how much influence the habit of duha prayers has on the discipline of class XI students in the Man 2 Langkat religion. This research is a type of quantitative research. The data collection techniques used were questionnaire and observation techniques. Based on the product moment correlation test, it shows that the habit of duha prayers with the discipline of religious students in class XI Man 2 Langkat has a relationship of 48.3%. Based on a simple linear regression test, the effect of the habit of duha prayer on student discipline in this study obtained a percentage result of 23.3%. The remaining 76.7% is influenced by other factors outside of things that are not included in the research variables